2014
DOI: 10.1515/zkri-2013-1673
|View full text |Cite
|
Sign up to set email alerts
|

High pressure neutron and X-ray diffraction at low temperatures

Abstract: This paper presents a review of techniques and considerations in the design and construction of high pressure, low temperature diffraction experiments. Also intended as an introductory text to new high pressure users, the crucial aspects of pressure cell design are covered. The general classification of common designs, and a discussion into the key beam interaction, mechanical, and thermal properties of commonly used materials is given. The advantages of different materials and high pressure cell classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 159 publications
(189 reference statements)
0
13
0
Order By: Relevance
“…Neutron scattering studies on large single crystals of several cubic millimetres are frequently performed in gas-pressure and clamp cells (Klotz, 2013;Ridley & Kamenev, 2014). There have been relatively few efforts to use other high-pressure devices for single-crystal neutron measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Neutron scattering studies on large single crystals of several cubic millimetres are frequently performed in gas-pressure and clamp cells (Klotz, 2013;Ridley & Kamenev, 2014). There have been relatively few efforts to use other high-pressure devices for single-crystal neutron measurements.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important as previous reports have suggested that mechanical grinding may also induce disorder in these samples 44 . The larger sample volume used in pressure cells for neutron diffraction studies 45 also allow for a more representative diffraction pattern than can be obtained from a focussed X-ray beam in a diamond anvil cell. Figure 3 shows the patterns from the ordered and disordered boules in a vanadium sample container.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, an additional advantage of this design is that it allows the pressure to be changed to smaller, more stable and controllable increments than in miniature DACs based on two-threaded connections. 6,7 The optimal type of the thread for axial load engineering applications is a buttress thread. In the absence of any other alignment mechanisms, the buttress thread aids the alignment of the anvils because the flank supporting the load is nearly perpendicular to the axis of the thread.…”
Section: D-dac Designmentioning
confidence: 99%
“…Typically, Merrill-Bassett type cells 2 are used for such diffraction measurements, but in recent years other cell designs have become increasingly popular in other areas of high-pressure research, such as the turnbuckle design first developed for use in high-pulsed magnetic fields 3,4 and for magnetic measurements in commercial magnetometers. 5,6 Although some miniature DACs for X-ray work have been constructed for use in cryogenic experiments, 7,8 there is a scope for further miniaturization to enable the use of open-flow cryogenic equipment which is practically extremely convenient and very commonly a) Electronic mail: K.Kamenev@ed.ac.uk available, but which has limited volume or cooling power compared to closed cryostats.…”
Section: Introductionmentioning
confidence: 99%